Magnetic Field Controlled Interlayer Coupling in MoS2 Field Effect Transistors. (3rd August 2021) - Yang, Yuying; Li, Alei; Wei, Mengmeng; Gong, Youpin; Qin, Wei
Abstract: The understanding of interlayer couplings should be paid much more attention owing to their importance in 2D materials with different layers. Here, through changing the number of layers, the tunability of interlayer coupling by external magnetic field in 2D material based field effect transistors is studied. External magnetic field can increase triplet electron‐hole (e‐h) pairs to promote interlayer coupling, where larger source‐drain current is induced. Moreover, increasing the gate voltage or source‐drain voltage, dipole–dipole interaction among the layers will be enhanced to weaken the tunability of source‐drain current by magnetic field. This result reveals the magnetic field dependence of interlayer couplings in 2D materials and provides a guidance to develop new functional 2D material devices. Abstract : Interlayer coupling plays an important role in 2D materials. External magnetic field can increase the ratio of triplet electron‐hole pairs to strengthen interlayer coupling in MoS2 field effect transistors. Via increasing the source and drain voltage or gate voltage, the tunability of the source and drain current by the magnetic field is suppressed.